O tema das quotas para afrodescendentes em concursos públicos - GODOY, ARNALDO SAMPAIO DE MORAES (Revista da AJURIS - Qualis A2, 2013)
O artigo discute a constitucionalidade de eventual regra que fixe cotas para afrodescendentes em concursos públicos, no contexto da Política Nacional de Promoção da Igualdade Racial. Tem como pano de fundo o problema histórico da discriminação, isto é, a escravidão. Discorre sobre a eliminação de qualquer fonte de discriminação e desigualdade raciais, direta ou indireta, mediante a geração de oportunidades. Trata também de política de cotas nas escolas públicas no ensino superior. Discorre sobre cotas raciais e cotas sociais. ABSTRACT: The paper discusses the constitutionality of a possible statute that provides shares for afrodescendants on Brazilian civil service exams, in the context of a national policy toward racial equality. It has as a backdrop the historical problem of the discrimination, that is, slavery. The paper goes into the elimination of any source of discrimination and racial inequality, direct or indirect, towards the promotion of opportunities. The paper also deals with the politics of afrodescendants shares in public universities. It finally considers racial and social shares for afrodescendants.